Postprandial Glycaemic and Insulinaemic Responses after Consumption of Activated Wheat and Triticale Grain Flakes - Laila Meija; Guna Havensone; Aivars Lejnieks (Journal of Nutrition and Metabolism)
Increasing evidence shows that whole grain consumption is protective against metabolic disorders. Protective bioactive substances of whole grains include fibre and antioxidants. Activation of grains can increase the amount of phenolic compounds and their bioavailability, but there is little evidence about their effect on glycaemic and insulinemic responses. Therefore, the aim of this study was to investigate glycaemic and insulinemic responses after consumption of flakes made from activated wheat and activated triticale grains. Eighteen healthy subjects (7 men and 11 women) were given activated wheat or activated triticale flakes. As a reference, a standard glucose solution was used. Plasma glucose and serum insulin were measured during 120 minutes. Both, activated wheat and activated triticale flakes, show improved glycaemic profile, inducing a lower and more stable glycaemic response. However, statistically significant differences in insulin response were found only in the group who have taken activated triticale flakes and not in the group who have taken activated wheat flakes. Activated triticale flakes induced lower insulin response in all postprandial phases and a more stable concentration of insulin. Thus, activated triticale flakes could be beneficial for the prevention and treatment of metabolic disorders.